AVALIAÇÃO DA SATISFAÇÃO DOS EXPOSITORES E VISITANTES DA TEC-E-INOVA 2008 - Kuhn, Ivo N.; Tizotte, Aline L.; Zortéa, Giovan; Zamberlan, Luciano; Froemming, Lurdes M. (Salão do Conhecimento, 2013)
Resumo